MULTILINGUAL EDUCATION AND COGNITIVE DEVELOPMENT: BALANCING MOTHER TONGUE MAINTENANCE AND ACADEMIC ACHIEVEMENT - Roni Subhan; Chenda Dara; Dara Vann (International Journal of Educatio Elementaria and Psychologia, 2026)
Multilingual education has become an increasingly important educational approach for addressing linguistic diversity while promoting cognitive development and equitable academic achievement. Continuing debates regarding the role of mother tongue maintenance alongside second-language acquisition have generated contrasting perspectives on how multilingual instruction influences learners’ cognitive growth and educational performance. This study aimed to examine the relationship between multilingual education, mother tongue maintenance, cognitive development, and academic achievement within linguistically diverse school settings. A mixed-methods sequential explanatory design was employed involving 1,180 students from fifteen multilingual primary and lower secondary schools implementing different language instruction models. Quantitative data were collected using validated measures of mother tongue proficiency, second-language proficiency, executive functioning, metalinguistic awareness, cognitive flexibility, conceptual understanding, literacy achievement, and academic performance, and analyzed through multilevel modeling, structural equation modeling, mediation analysis, and hierarchical regression. Qualitative evidence was obtained through interviews, classroom observations, focus group discussions, and institutional document analysis, followed by thematic interpretation. Findings revealed that sustained mother tongue maintenance significantly strengthened conceptual understanding, metalinguistic awareness, executive functioning, literacy development, and overall academic achievement. Teacher multilingual competence and family language support further enhanced multilingual learning by reinforcing classroom participation and cognitive flexibility. Results indicate that multilingual education achieves optimal outcomes when linguistic diversity is integrated into coherent instructional practices, supportive language policies, and culturally responsive teaching. The proposed framework provides practical guidance for developing multilingual educational systems that simultaneously preserve linguistic heritage and promote cognitive excellence.